Inventarisasi Emisi Gas Rumah Kaca di TPA Benowo Menggunakan Metode IPCC - Muhammad Ilham Muzakki; Raden Kokoh Haryo Putro (Jurnal Serambi Engineering, 2024)
In 2010, Indonesia ranked fourth in terms of waste generation. As a result, the waste sector is estimated to potentially contribute 296 Mt CO2 eq (10.32%) of total greenhouse gas (GHG) emissions by 2030, with a projected annual growth rate of 6.3% using the business-as-usual (BAU) projection from 2010 to 2030. Around seventy per cent of all waste is organic, making household waste one of the main sources of urban waste. This study was conducted at the Benowo Landfill in the city of Surabaya. The SNI 19-3964-1994 method was used to sample the composition and generation of waste at the landfill. Waste generation projections were made up to 2030, taking into account population growth. This study compares methane gas emissions from three scenarios: Scenario 1, direct landfilling of waste; Scenario 2, waste reduction through composting and 3R processing; and Scenario 3, waste processing at the landfill through gasification. Based on inventory calculations using the 2006 IPCC guidelines, the landfill scenario produces the highest greenhouse gas emissions (CO2 and CH4), with the highest CH4 emissions and the lowest CO2 emissions. The gasification scenario has the highest CO2 emissions and the lowest CH4 emissions due to the use of aerobic systems and combustion.